Metastatic Insulinoma Following Resection of Nonsecreting Pancreatic Islet Cell Tumor - Anoopa A. Koshy MD; Ilyssa O. Gordon PhD; Thuong G. Van Ha MD; Edwin L. Kaplan MD; Louis H. Philipson MD, PhD (SAGE Publishing, 2013)
A 56-year-old woman presented to our clinic for recurrent hypoglycemia after undergoing resection of an incidentally discovered nonfunctional pancreatic endocrine tumor 6 years ago. She underwent a distal pancreatectomy and splenectomy, after which she developed diabetes and was placed on an insulin pump. Pathology showed a pancreatic endocrine neoplasm with negative islet hormone immunostains. Two years later, computed tomography scan of the abdomen showed multiple liver lesions. Biopsy of a liver lesion showed a well-differentiated neuroendocrine neoplasm, consistent with pancreatic origin. Six years later, she presented to clinic with 1.5 years of recurrent hypoglycemia. Laboratory results showed elevated proinsulin, insulin levels, and c-peptide levels during a hypoglycemic episode. Computed tomography scan of the abdomen redemonstrated multiple liver lesions. Repeated transarterial catheter chemoembolization and microwave thermal ablation controlled hypoglycemia. The unusual features of interest of this case include the transformation of nonfunctioning pancreatic endocrine tumor to a metastatic insulinoma and the occurrence of atrial flutter after octreotide for treatment.